Intervensi Perilaku untuk Mengurangi Gejala Kecemasan pada Lansia di Desa Mekarsari RW 12 Tambun Selatan - Sephia Chaerunisa; Sarita Candra Merida; Rospita Novianti (Devotion : Jurnal Pengabdian Psikologi, 2022)
In general, Anxiety is characterized by worry, anxiety, fear, anxiety, restlessness, panic, and other uncomfortable feelings. If the elderly who experience anxiety, it will be declining health which influences financial, social and emotional. Behavior Intervention for this activity uses psychoeducation and relaxation exercise. Psychoeducation to explain anxiety disorder experienced by the elderly by using short lectures and discussion between participants. After that, participants begin relaxation exercises, to release muscle tension in each body. Participants in this activity were the elderly aged 60-65 years totaling five people. After being given psychoeducation, it was able to increase the knowledge of all participants about the symptoms and the factors causing anxiety. Through relaxation exercises, helping to practice when the symptoms of anxiety appear so that they become relaxed, more comfortable, less nervous, focused and confident. It can be concluded that the subjects who participated in this intervention had an increased understanding of the symptoms and factors causing anxiety. Skills for coping anxiety were also increased through the relaxation exercises provided.